Kvalita výkonu veřejné správy je bezprostředně spjata s problematikou etiky ve veřejné správě - Nečadová, Věra (Univerzita Pardubice, 2013)
When discussing the quality of public administration performance, it is necessary to comprehend its direct relation to the issues of ethics in the sphere of public administration. Public administration performance consists in the service for citizens. The general principles and value criteria in public administration performance are law observance, work quality, efficiency and ethics (special attention is particularly paid to the observance of objectivity and equal approach). Other fundamental principles are information transparency, being not susceptible to influence, incorruptibility and integrity. The employees should also take a keen interest in keeping the good reputation of the office where they work. If we manage, in a suitable manner, to combine the aspects presented above with the modern methods and approaches of public administration management, with high-quality education of public administration employees, with sensible management of regional development in dynamically changing conditions, and with effective application of information and communication technologies, then there is a precondition for achieving higher efficiency of public administration performance.
The quality of public administration performance is closely related to the issues of ethics in public administration
Keywords: public administration; requirements for public administration employees; ethical values; moral standards; ethical code; corruption; code of conduct; professionalism